La mediación como medio alternativo de resolución de conflictos provenientes de la Sociedad Conyugal - Avila Lascano, Mercedes (2024)
Mediation is considered as an alternative means of conflict resolution and it is recognized in the article 190 of the Constitution of the Republic of Ecuador of 2008 as well as in the article 43 of the Mediation and Arbitration Law of 2006. This regulation established that the parties by mutual agreement may submit their controversies to a neutral third party called a mediator who will help to solve them considering the principle of willingness, impartiality, and confidentiality. In this context, in Ecuador, the Conjugal Society is a marital property regime regulated by the Ecuadorian Civil Code. This regime determines how the assets acquired during the marriage are administered and disposed of as well as the responsibilities for the incurred debts. The general objective established in this research was to develop a legal and doctrinal study on mediation as an alternative means of conflict resolution in the Conjugal Society. For this, the methodology applied in this study was a descriptive and exploratory with a mixed approach. The measurement instruments used were a structured survey and an interview guide. The target population of this research consisted of 30 people who were legal professionals, citizens in general, and five legally accredited mediators. The results obtained revealed that 83% of the surveyed people know about mediation procedures, meanwhile, in the interview part, 97% considered that the Mediation and Arbitration Law should be reformed and contain a section on Conjugal Society cases, considering that it is an effective mechanism in the resolution of conflicts. However, since it does not currently exist, a reform is proposed where admissibility criteria are established to consider mediation as an alternative means of conflict resolution arising from the Conjugal Society.